2021
DOI: 10.3389/fendo.2021.760901
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Distant Metastasis Is Associated With Histopathological Subtype of Pediatric Papillary Thyroid Cancer - a Retrospective Analysis Based on SEER

Abstract: ObjectiveChildren with papillary thyroid cancer (PTC) have a higher invasive rate and distant metastasis rate, but the mortality rate is lower with unknown reasons. The majority of PTC cases comprise classical papillary thyroid carcinoma (CPTC) and follicular variant papillary thyroid carcinoma (FVPTC). This study aimed to determine the relationship between histopathological subtype and rate of distant metastasis and investigate factors influencing distant metastasis in pediatric PTC.MethodsA total of 102,981 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…From our clinical data, we found age and lymph node metastases were important prognostic indicators of PPTC which are matched with previous findings 24- 27 . In our PM group, the age of 16 was the cutoff for predicting recurrence-free survival (RFS), as nine of the 12 recurrent patients were younger than 16.…”
Section: Discussionsupporting
confidence: 91%
“…From our clinical data, we found age and lymph node metastases were important prognostic indicators of PPTC which are matched with previous findings 24- 27 . In our PM group, the age of 16 was the cutoff for predicting recurrence-free survival (RFS), as nine of the 12 recurrent patients were younger than 16.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this, about age and tumor size, there is no agreement regarding specific cut-offs [ 19 , 20 ]. Furthermore, in few studies, histological subtypes were considered [ 21 ], although their importance was remarked in the last edition of the WHO classification.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studying the incidence trend of childhood TC might better reflect the prevalence of this disease in the population. In addition, some types of childhood TC are more prone to have lymph node metastasis than in adults, with a wider range of lesions and leading a worse prognosis [ 9 , 10 ]. Currently, many studies have reported the incidence and prevalence of TC in children and adolescents worldwide, with the age ranges from 0 to 20 years [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%